RANCANG BANGUN POMPA TENAGA GRAVITASI UNTUK MENDUKUNG KEBERLANJUTAN PENGAIRAN DALAM SEKTOR PERTANIAN DI KECAMATAN LIMBANGAN - M Aldi Gofarizkia; Mohammad Herdyn Hidayatullah; Tizar Mei Luthfi; Harieza Reandi Putra Rahmantito; Sukarno Budi Utomo (PT. Hasba Edukasi Mandiri, 2025)
This study aims to design and develop a gravity-powered water pump as a solution to irrigation problems in Gondang Village, Limbangan District, Kendal Regency. The village’s mountainous topography makes it difficult for farmers to channel water from the river to agricultural land located at higher elevations. The gravity-powered pump is designed without using external energy sources such as electricity or fuel, instead utilizing the potential energy of water flow (gravity). The methodology includes field studies, literature reviews, community needs surveys using questionnaires, anthropometric measurements for ergonomic design, as well as conceptualization, prototyping, and testing stages. The pump design takes into account technical, functional, ergonomic, and safety aspects, along with SWOT analysis and production cost calculations. As a result, the pump is capable of delivering water from lower to higher areas automatically and efficiently, with a production cost of Rp 700,000 and a recommended selling price of Rp 800,000. The project concludes that gravity-powered water pumps can serve as an effective, energy-efficient, environmentally friendly, and economical solution to help improve the productivity of the agricultural sector in remote areas with limited access to water.